Automating the Production of Communicative Gestures in Embodied Characters - Ravenet, Brian; Pelachaud, Catherine; Clavel, Chloé; Marsella, Stacy (Frontiers in Psychology, 2018)
In this paper we highlight the different challenges in modeling communicative gestures for Embodied Conversational Agents (ECAs). We describe models whose aim is to capture and understand the specific characteristics of communicative gestures in order to envision how an automatic communicative gesture production mechanism, inspired by these theoretical foundations on human embodied cognition and on the related work, could be built. Gesture characteristics (e.g. shape of the hand, movement, orientation, timing with respect to the speech...) should convey the desired meaning. We present different endeavors that tackle the issue of computing where to place a gesture, which shape the gesture takes and how gesture shapes evolve through time. We focus on a particular model based on theoretical frameworks on metaphors and on how people represent and transfer physical properties from a concept to another to create specific gestures.